PERENCANAAN PELAT BANGUNAN GEDUNG DENGAN METODE MARCUS - Maricar, Shyama (MEKTEK, 2005)
This paper explained more circumstantial of planning lisp at a building by using Method of Marcus, load and bone volume of the lisp were calculated by using method Marcus. In this method, the flatten load is calculated using tables and the point load is calculated with formula and table.The result shows that by using formula 1,2 MD + 1,6 ML of combination load, the maximum encumbering values were obtained for Mlx, Mly,Mtx, Mty.From the reinforcement calculation, the reinforcement of field in x direction use Ø 12 – 150 mm and for the fulcrum use Ø 12 – 150 mm. In y direction, reinforcement of the field and the fulcrum use Ø 14 – 150 mm. For the convenience, The reinforcement with Ø 14 – 150 mm is used for x and y direction.